2005
DOI: 10.1590/s1517-83822005000200001
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological analyses of water from hemodialysis services in São Luís, Maranhão, Brazil

Abstract: Rigorous control of water quality in hemodialysis services is extremely important in order to guarantee a better quality of life of the patients submitted to this treatment. The lack of adequate water monitoring has caused the death of various patients in the past. The objective of the present study was to determine the physicochemical and bacteriological characteristics of water used by hemodialysis services in hospitals of the city of São Luís, Maranhão, Brazil. Bacteriological analyses included the membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 3 publications
4
13
0
3
Order By: Relevance
“…We isolated genus Pseudomonas at 52.8% in agreement with other authors [21–23]. These bacteria are able to grow rapidly even in sterile water and dialysis fluids.…”
Section: Discussionsupporting
confidence: 90%
“…We isolated genus Pseudomonas at 52.8% in agreement with other authors [21–23]. These bacteria are able to grow rapidly even in sterile water and dialysis fluids.…”
Section: Discussionsupporting
confidence: 90%
“…Other species found in the water from the machines, in order of decreasing frequency, were: 13 P. aeruginosa, eight S. epidermidis and P. stutzeri, two S. maltophilia and K. pneumoniae and one B. cereus, P. putida and F. odoratum. LIMA et al 23 reported the isolation of S. maltophilia and B. cepacia in water samples taken directly from points before and after water treatment and from the kidney machines.…”
Section: Burkholderia Cepaciamentioning
confidence: 99%
“…They are exposed to approximately 120L of treated water in each session (4, 12, 16, 18, 22, 23). Water is separated from the blood of the patient by a semipermeable membrane, which may enable direct access of contaminants that might be present in the water (6, 9, 10, 11, 22).…”
mentioning
confidence: 99%
“…Water is separated from the blood of the patient by a semipermeable membrane, which may enable direct access of contaminants that might be present in the water (6, 9, 10, 11, 22). Monitoring and maintenance of water treatment systems are important to assure its chemical and microbiological quality and to prevent additional risks to the patients (4, 6, 9, 10, 11, 12, 14, 15, 16, 18, 22, 23). …”
mentioning
confidence: 99%
See 1 more Smart Citation